THE EFFECT OF THE HARZANDLER'S SIBLING MAGOMINI ON THE SUBJECT - O‘rmonov To‘lqinjon Kimsanovich (Journals Park Publishing, 2024)
The article highlights the important aspects of child development and, later, how few places they find in social processes and cooperate. The article also outlines the scientific research of psychologists on sibling relationships.
Keywords: Sibling, child, child, relationship, scientific research, ability research, father, mother.